Camel Brucellosis: Seroprevalence, Associated Risk Factor, and Public Health Perceptions in Arero District of Borena Zone, Southern Ethiopia - Wario Waji Edema; Gemechu Chala Hunderra; Sultan Abda Neja (Veterinary Medicine International)
A cross-sectional study was conducted to determine the seroprevalence and potential risk factors of camel brucellosis and to assess public health awareness of the disease in the selected kebele of Arero District, Borena Zone, Southern Ethiopia. A total of 313 blood samples were collected from selected camels using a systematic random sampling technique. The serum samples underwent initial screening for brucellosis using the rose Bengal plate test (RBPT), with further confirmation through the indirect enzyme-linked immunosorbent Assay (i-ELISA). The overall seroprevalence of camel brucellosis was 7.66% using RBPT and 2.24% using i-ELISA. Univariable and multivariable logistic regression analyses revealed significant associations; female camels (OR = 30.16, p=0.05) and mixing camels with other animal species (OR = 0.019, p=0.001 by i-ELISA) were significantly linked to camel seropositivity for Brucella infection. Assessment of public health perception and awareness from 227 owners indicated limited awareness; most respondents lacked knowledge about brucellosis (94.27%), 82.82% were unaware of raw meat risks, 94.27% did not know about brucellosis being zoonotic, and 18.94% consumed raw milk with blood. The majority (94.71%) practiced bare-handed calving, with 93.39% handling abortion materials, rarely isolating infected camels. The study found a moderate prevalence of brucellosis among camels in the study areas. Lack of implemented control strategies, combined with local pastoral practices, could potentially contribute to disease spread. Therefore, there should be continuous efforts of the disease control strategy at the animal level, community awareness creation, separation of infected camels from health heard, and avoiding mixing a camel with other animal species.